Cuidado com aquele bizarra! Performatividades desobedientes de gênero na artevida de corpas dissidentes do binário - Martins, Ricardo Marinelli (2023)
The proposal of this research was to produce a self-oreographic cartography of Princess Ricardo Marinelli and between crossing it with the selfographies of two other non-binary artist subjectivities (Stefano Belo and Cali Ossani), betting on a poetics and a narrative of the meeting. For this we resorted to the methodological parameters of cartography (Deleuze-Guarri, 1995, 1996, 1997a, 1997b; Rolnik, 1996, 2018; Barros, 2015; Aguiar, 2010). Along with this, we resorted to “performative research”, in which we find support to actually build selfographically thinking (Haseman, 2015). The challenge has always been to bring the possibilities of academic writing closer to those of art creation, daunting the boundaries between art, science and what we call life. In this endeavor helps us the theory of gender performance (1990) developed by philosopher Judith Butler in the 1990s and pointing out the performative character of the genre, the theory is based on three main points: 1. The concept of performative acts of language, by John Austin (1990); 2. The understanding of citation, of Jacques Derruda (1991; 2004); and finally, 3. Understanding of performance recognized in its dimension of production of the real. Along with this conceptual elaboration, we were interested in realizing how the intersection of these performative dimensions happen in the gesture, the choreography of the materiality of the body, and therefore, in the processes of subjectivation, especially to perceive and make visible what we are calling performance kuir. In this context the proposal of the contrarssexuality of Paul Preciac (2014) to understand and explain that I am part of a flood of bodies that re/exist challenging the binary genre and its compulsory dynamics. A horde that is not afraid to inhabit the uncertain, the little defined, the blurred, the strange. An swarm that does not swallow the alleged truth that humanity is divided solely between men and women. And so I have no choice but to update their survival strategies daily and daily. And we are spiraling time, connecting with ancestments and producing unthinkable future. In the midst of bizarre and chaos.